Application of Soft Matrix Theory in Decision Making - Sarfraz Ahmed; Tapan Boruah (International Journal of Mathematics And its Applications, 2019)
In this paper, the traditional soft set theory is expanded to be a fuzzy one the fuzzy membership is used to describe parameter-approximate elements of fuzzy soft set. We then define products of soft matrices and their properties. We finally construct a soft max-min decision making method which can be successfully applied to the problem that contains uncertainties.